SIKOPYAH WATER PRESERVATION BASED ON REGIONAL REGULATION OF PURBALINGGA REGENCY NUMBER 2 YEAR 2014 CONCERNING PROTECTION AND MANAGEMENT OF LIVING ENVIRONMENT - Ramadhan, Naufal Sajid; Soediro, Soediro; Hidayahh, Astika Nurul (UMPurwokerto Law Review, 2020)
Sikopyah Springs is a source of clean water supply for the people of Serang Village, Karangreja District, Purbalingga Regency which is a member of the Village Owned Enterprises (BUMDes) and is also used to meet the needs of the community outside the village managed by the Regional Water Company (PDAM). With the increasing need for clean water, the proper management of water resources is needed. Some things that can be known in relation to the management of the Sikopyah Springs are first by knowing the spring management program carried out by the community in Serang Village, second by analyzing demographic and topographic data from the Serang Village community in an effort to manage Sikopyah Springs, and third by getting factors both a booster and an obstacle in the management of springs in Serang Village. The study was conducted using normative juridical research methods and data specifications using descriptive methods, then analyzed using qualitative data analysis methods. The study results show that conservation efforts, namely the use, protection, and preservation of the Sikopyah Springs, have been carried out by the people of Serang Village. Keywords: Environmental Conservation, Sikopyah Springs, Regional Policy Â